Juridical Analysis Of Evaluation And Supervision Of The Use Of Rights On Land Management Rights (HPL) To Strengthen Legal Certainty - Michael Hasiholan Hutapea; Soerya Respationo; Sayid Fadhil; Erniyanti Erniyanti (FKIP, Universitas Palangka Raya, 2023)
The granting of Batam Island management rights is stated in Article 6 paragraph (2) letter a of Presidential Decree Number 41 of 1973, stating that all land areas located on Batam Island are handed over with management rights to the Chairman of the Batam Island Industrial Area Development Authority (later called the Batam Authority). Referring to Article 4 of Government Regulation Number 46 of 2007, Management Rights over land under the authority of the Batam Authority and Management Rights over land under the authority of the Batam City Government located in the Batam Free Trade Zone and Free Port are transferred to BP Batam by statutory regulations. Invitation. The areas in question are Batam Island, Setokok Island, Watch Island, Nipah Island, Galang Baru Island, Rempang Island, and Galang Island. However, replacing the subject of management rights does not end existing rights on Management Rights land; these rights remain in effect until the validity period ends. Thus, currently, Batam City Management Rights are owned by BP Batam. Problems with management rights also occur in the community of Batam City. This is, of course, a result of the development of Batam City, where the land rights are mainly allocated to industrial areas, housing (residential), government, and protected forests. One of the purposes of granting Management Rights to BP Batam was to accelerate investment. However, during the process, it was discovered that the land allocated to a third party (Investor) had yet to be physically developed as agreed upon at the time of allocation. This then becomes the basis for BP Batam to carry out evaluation and control over land that is not built and built not by its intended use.